2020
DOI: 10.32508/stdjsee.v4i1.525
|View full text |Cite
|
Sign up to set email alerts
|

Application of groundwater quality index (GWQI) and GIS in groundwater quality zoing in Pleistocene aquifer in Phu My town, Ba Ria – Vung Tau province

Abstract: Pleistocene aquifer is exploited for many purposes, including irrigation, domestic, production, and livestock use in Phu My town, Ba Ria – Vung Tau province. Groundwater Quality Index (GWQI) method combined with Geographic Information System (GIS) foundation is applied to determine the spatial variation as well as the suitability of groundwater in the study area. Water quality parameters in this study include pH, TDS, total hardness, Cl-, F-, NH4+, NO3-, SO42-, Pb2+, and Fe2+ were selected for analyzing from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…The causes of groundwater pollution at the GW24 site may be due to seawater intrusion and improper wastewater and waste management. Compared with other studies, the overall groundwater quality in Ca Mau was better than that in Ha Nam province (GWQI 67-369) [33], but it was worse than the groundwater quality in Ba Ria -Vung Tau [19] and the groundwater quality in Dong Thap, An Giang, Hau Giang, and Kien Giang [15]. The difference in results of GWQI in various areas in the current and former studies could be from the input data.…”
Section: Classification Of Groundwater Quality In the Study Areacontrasting
confidence: 54%
See 3 more Smart Citations
“…The causes of groundwater pollution at the GW24 site may be due to seawater intrusion and improper wastewater and waste management. Compared with other studies, the overall groundwater quality in Ca Mau was better than that in Ha Nam province (GWQI 67-369) [33], but it was worse than the groundwater quality in Ba Ria -Vung Tau [19] and the groundwater quality in Dong Thap, An Giang, Hau Giang, and Kien Giang [15]. The difference in results of GWQI in various areas in the current and former studies could be from the input data.…”
Section: Classification Of Groundwater Quality In the Study Areacontrasting
confidence: 54%
“…Former studies also measured pH values in groundwater. For example, pH in groundwater wells in the Ho Chi Minh City area was in the range of 3.4-7.4 [28], in the areas of Ba Ria -Vung Tau, it was 4.30-7.80 [19], and in the areas of Ha Nam Province, it was 6.19-7.33 [33]. A previous study also found that groundwater pH in the Mekong Delta of Vietnam was in the range of 6.54-7.76 [15].…”
Section: Physical and Chemical Characteristics Of Groundwater In The ...mentioning
confidence: 99%
See 2 more Smart Citations